Clinical Stage at Presentation and Obesity in South Indian Breast Cancer Patients-A Cross-Sectional Analysis (GAIMS Journal of Medical Sciences, 2024)
Background: Breast cancer stands as a formidable global health challenge. While obesity is recognized as a risk factor, its specific influence on the clinical stage at presentation remains unclear, especially in populations with unique genetic and environmental factors, such as South India. This research aims unravel the intricate links between obesityand clinical stage at presentationin South Indian breast cancer patients for tailored screening and management strategies in this distinct demographic.Material and methods: This cross-sectional study was done at the Department of Physiology, Government Medical College, Thrissur, Kerala, India, on newly diagnosed female breast cancer patients. The menopausal status and body mass index of the patients was taken and classified as per the WHO Asian Classification. The clinical staging was assessed and classified by American Joint Committee on Cancer (AJCC) criteria. Statistical analysis, including chi-square tests, assessed the association between BMI status, menopausal statusand clinical staging.Results: Out of 93 patients, 62.8% were obese. Underweight patients mostly presented at Stage IIIa (50%), while obese women presented atStage IIa. Linear regression showed no significant link between obesity and higher cancer stages. (p=0.247) Additionally, BMI and clinical stage analyses in premenopausal and postmenopausal groups revealed non-significant results (p = 0.750 and p = 0.174, respectively).Conclusion: This study does not establish a supportive relationship between obesity and increased clinical stageof breast cancer presentation in South Indian women. The findings challenge the expected link between obesity and advanced stage. This deviation underscores the need for further exploration of the intricate interplay between obesity and regional factors influencing breast cancer in this population.